1980
DOI: 10.1007/bf00336677
|View full text |Cite
|
Sign up to set email alerts
|

A computed tomographic prolective trohoc study of chronic schizophrenics

Abstract: The maximal width of the third ventricle, the maximal distance between the outer tips of the anterior horns, and the number of enlarged cerebral sulci on the two highest CT slices were measured in 68 chronic schizophrenic patients on cranial computed tomograms in order to detect a possible enlargement of the cerebrospinal fluid (CSF) filled intracranial spaces. These results were compared with values obtained from a control group which was formed in accordance with definite exclusion criteria and matched-pair … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

1982
1982
1992
1992

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 7 publications
1
6
0
1
Order By: Relevance
“…Andreasen et al (5) revealed some impairment in the sensorium and a preponderance of "negative symptoms", which are thought equivalent to "Type I1 syndrome" (6). Other investigators have revealed similar findings (7-ll), while others found no morphological abnormalities in schizqhrenics (12)(13)(14)(15). We have recently reported that the bifrontal and occipital regions of chronic schizophrenics have significantly lower densities compared with controls (16, 17).…”
supporting
confidence: 73%
“…Andreasen et al (5) revealed some impairment in the sensorium and a preponderance of "negative symptoms", which are thought equivalent to "Type I1 syndrome" (6). Other investigators have revealed similar findings (7-ll), while others found no morphological abnormalities in schizqhrenics (12)(13)(14)(15). We have recently reported that the bifrontal and occipital regions of chronic schizophrenics have significantly lower densities compared with controls (16, 17).…”
supporting
confidence: 73%
“…Johnstone et al (1976,1978), in CT-scan studies, observed an increase in mean lateral ventricular size in a group of institutionalized schizophrenic patients. This finding has been replicated by other studies (Weinberger et al, 1983) but challenged by others (Gluck et al, 1980;Jernigan et al, 1982). More recently, several carefully controlled MR I studies demonstrated pathomorphology at the first psychotic episode in untreated schizophrenic patients, third ventricle enlargement being the most prominent anomaly (Lieberman, 1991;Nasrallah, 1991).…”
Section: Introductionmentioning
confidence: 56%
“…However, our research group has reported that a population of chronic schizophrenics in a clinical research centre inpatient ward did not exhibit a statistically significant increase in lateral ventricular size Jernigan et al (1982). Whereas others (Benes et al 1982;Gluck et al 1980;Trimble & Kingsley, 1978), have reported similar findings, most investigators (Andreasen et al 1982 a;Boronow et al 1985;Cambell et al 1979;Famuyiwa et al 1979;Frangos & Athenassenas, 1982;Gattaz et al 1981;Golden et al 1980;Johnstone et al 1978;Nasrallah et al 1982 a;Nyback et al 1982;Okasha & Madkour, 1982;Pearlson & Veroff, 1981;Reveley et al 1982;Rieder et al 1979;Schulz et al 1982;Tanaka et al 1981;Van Kammen et al 1983;Weinberger et al 1979a, Woods & Wolf, 1983 have reported, with variable prevalence, increases in lateral ventricular size, third ventricular size, cortical atrophy, or cerebellar atrophy.…”
Section: Introductionmentioning
confidence: 65%
“…Brain computerized tomography in chronic schizophrenic patients is a topic which has attracted a great deal of attention in recent years (see Jernigan (1986) for review). Numerous investigators have suggested that lateral ventricular enlargement, third ventricular enlargement, sulcal atrophy, and/or cerebellar atrophy can be found in a certain proportion of patients who carry the diagnosis of schizophrenia (Andreasen et al 1982 a, b;Benes et al 1982;Boronow et al 1985;Cambell et al 1979;Famuyiwa et al 1979;Frangos & Athenassenas, 1982;Gattaz et al 1981;Gluck et al 1980;Golden et al 1980;Jernigan, 1986, Jernigan et al 1982Johnstone et al 1978, Luchins et al 1980Luchins & Meltzer, 1986;Nasrallah et al 1982 a, 6, c;Nyback et al 1982;Okasha & Madkour, 1982;Owens et al 1985;Pearlson & Veroff, 1981;Potkin et al 1983;Reveley et al 1982;Rieder et al 1979;Schulz et al 1982;Schulz et al 1983;Tanaka et al 1981;Trimble & Kingsley, 1978;Van Kammen et al 1983;Weinberger et al 1979 a, b, c;Weinberger et al 1980 a, b;Weinberger et al 1981;Weinberger et al 1982;Woods & Wolf, 1983). However, our research group has reported that a population of chronic schizophrenics in a clinical research centre inpatient ward did not exhibit a statistically significant increase in lateral ventricular size Jernigan et al (1982).…”
Section: Introductionmentioning
confidence: 99%